Fetal Brain Border Detection from MRI using Chain Code Algorithm - Gayathri, S.P; Somasundaram, K; Shankar, R.Siva (International Journal of Computer Sciences and Engineering, 2025)
Magnetic Resonance Imaging of fetal brain facilitates to evaluate in-utero fetal brain development. Segmentation of fetal brain from MRI is a challenging task due to significant changes in terms of geometry as well as tissue morphology. In order to make ease of segmentation, fetal brain border is detected using chain code algorithm. Detected brain border is used further through in which query images will be extracted from fetal MRI database. This work will be extended with feature extraction and 3D modeling of fetal brain in a little while